ASME 2015 13th International Conference on Nanochannels, Microchannels, and Minichannels 2015
DOI: 10.1115/icnmm2015-48508
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption-Based Thermal Rectifier

Abstract: Controlling thermal energy transport (thermal diode) for the desired direction is crucial to improve the efficiency of thermal energy transport, conversion, and storage systems as electrical diodes significantly impact on modern electronic systems. The degree of thermal rectification is measured by the difference between the heat transfer rate in favorable and unfavorable directions to the heat transfer rate in the unfavorable direction. A gas-filled, nano-gap structure with two different surface coatings is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Recent investigations of thermal rectification have covered different heat transfer(HT) modes including conduction [24,25], convection [26] and radiation [27,28,29,30,31,32,33,34]. We describe the main current trends in the following paragraphs and more extensive reviews can be found in [8,35].…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations of thermal rectification have covered different heat transfer(HT) modes including conduction [24,25], convection [26] and radiation [27,28,29,30,31,32,33,34]. We describe the main current trends in the following paragraphs and more extensive reviews can be found in [8,35].…”
Section: Introductionmentioning
confidence: 99%
“…From that point forward, several investigations have been performed to understand which systems can exhibit thermal rectification [6] and have introduced the concepts of numerous innovative devices like thermal transistors [7][8][9][10], thermal logic circuits [11][12][13][14][15] and thermal diodes [16][17][18][19][20][21]. Recent investigations of thermal rectification have covered different heat transfer(HT) modes including conduction [22,23], convection [24] and radiation [25][26][27][28][29][30][31][32]. We describe the main current trends in the following paragraphs and more extensive reviews can be found in [6,33].…”
Section: Introductionmentioning
confidence: 99%